Determinan Motivasi Berwirausaha Pada Sarjana Perguruan Tinggi Swasta: Studi Deskriptif Di Kabupaten Blora - Ahmad Sadid (Genius: Jurnal Ekonomi Dan Manajemen, 2025)
The low motivation to be entrepreneurial among private university graduates (PTS) is a serious challenge in Blora Regency, where the educated unemployment rate reaches 18.7% while only 7.2% of graduates choose to be self-employed. This study aims to describe the determinants of entrepreneurial motivation, identify dominant barriers, and formulate evidence-based policy recommendations. The research uses a qualitative approach with a descriptive type of research. Primary data sources were obtained from 45 private university graduates in Blora Regency who have graduated for at least one year with the status of job seekers, unemployed, or novice entrepreneurs, as well as key informants consisting of lecturers, student program managers, and community leaders. Data were collected through in-depth interviews, passive participant observations, and documentation studies, then analyzed using an interactive thematic model. The results showed that internal determinants included low self-efficacy (71.1%), low need for achievement (62.2%), and low risk tolerance (73.3%). External determinants include negative family support (62.2%), negative environmental subjective norms (68.9%), low access to capital (71.1%), and non-optimal role of educational institutions (80.0%). The dominant barrier is the systemic interaction between internal and external factors called  entrepreneurial double bind (77.8%). This study concludes that the entrepreneurial motivation of private university graduates in Blora is hampered by the complex interaction between individual psychological factors and socio-cultural pressures, so that an integrated intervention is needed that targets changes in social norms as well as strengthening individual capacity.